Electrochemical growth of flowerlike gold nanoparticles on polydopamine modified ITO glass for SERS application - Ye, Weichun; Wang, Daoai; Zhang, Hong; Zhou, Feng; Liu, Weimin (Electrochimica acta, 2010)
A functional biopolymer – polydopamine (Pdop) layer was easily modified on the surface of indium tin oxide substrates by spontaneous oxidative polymerization in a dopamine solution. The Pdop layer functions as a novel and promising protector for electrochemical growth of flowerlike gold nanostructures (AuNFs). Electrochemical investigations and SEM results demonstrate that Pdop coating is favored to rapid gold nucleation. The application of AuNFs in surface-enhanced Raman scattering is investigated by using rhodamine 6G as probe molecule. Its detection limit reaches as low as 10 −12 M. Pdop coating as a functional platform to prepare AuNFs is promising for potential applications in sensitive optical chemical sensors.